2014
DOI: 10.1111/apha.12263
|View full text |Cite
|
Sign up to set email alerts
|

Acylated and unacylated ghrelin inhibit doxorubicin‐induced apoptosis in skeletal muscle

Abstract: Collectively, our data demonstrated that acylated ghrelin administration suppresses the doxorubicin-induced activation of apoptosis and enhances the cellular signalling of autophagy. The treatment of unacylated ghrelin has similar effects as acylated ghrelin on apoptotic and autophagic signalling, suggesting that the effects of ghrelin are probably mediated through a signalling pathway that is independent of GHSR-1a. These findings were consistent with the hypothesis that acylated ghrelin inhibits doxorubicin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 58 publications
6
63
0
Order By: Relevance
“…The exact causes of muscle weakness and atrophy induced by doxorubicin remain poorly understood, and doxorubicin-treated rodents have been used to investigate these phenomena. In these models, muscle weakness and fiber alterations (proteolysis, autophagy, apoptosis) have been described, with variations depending on the mode of administration (intraperitoneal versus intravenous) and the type of muscle (soleus, extensor digitorum longus, heart, diaphragm) (Gilliam et al, 2009(Gilliam et al, , 2012(Gilliam et al, , 2013De Angelis et al, 2010;Smuder et al, 2011a,b;DirksNaylor et al, 2013;Kavazis et al, 2014;Yu et al, 2014). These studies show evidence that muscle fibers as well as the (n = 8).…”
Section: Resultsmentioning
confidence: 99%
“…The exact causes of muscle weakness and atrophy induced by doxorubicin remain poorly understood, and doxorubicin-treated rodents have been used to investigate these phenomena. In these models, muscle weakness and fiber alterations (proteolysis, autophagy, apoptosis) have been described, with variations depending on the mode of administration (intraperitoneal versus intravenous) and the type of muscle (soleus, extensor digitorum longus, heart, diaphragm) (Gilliam et al, 2009(Gilliam et al, , 2012(Gilliam et al, , 2013De Angelis et al, 2010;Smuder et al, 2011a,b;DirksNaylor et al, 2013;Kavazis et al, 2014;Yu et al, 2014). These studies show evidence that muscle fibers as well as the (n = 8).…”
Section: Resultsmentioning
confidence: 99%
“…We herein report, for the first time, that sleeve gastrectomy is associated with an upregulation of the autophagy-related genes Atg5 and Atg7 and the LC3B-II/I ratio as well as with a decrease in the autophagy inhibition marker p62, suggesting that the induction of autophagy after this surgical procedure improves hepatic lipid clearance via lipophagy. Ghrelin isoforms are involved in the regulation of autophagy in several tissues, including the adipose tissue, small intestine, skeletal muscle and the heart38616263. Mao and colleagues reported that ghrelin induces autophagy in the liver via the activation of the AMPK signalling pathway56, but the specific role of each isoform of the hormone remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory and others have reported that DOX accumulates in skeletal muscle in vivo 15,23 which results in an excessive reactive oxygen species production. This oxidative stress prompts peroxidation, protein carbonyl formation, proteolysis 9 , apoptosis upregulation 24 , enhanced autophagy signaling 8 , and nuclear DNA damage 25 . Of utmost consequence to cancer patients receiving DOX, skeletal muscle damage at the cellular level leads to decreased force production and increased fatigue 13,15 , and cancer patients receiving DOX report severe to debilitating fatigue 26 .…”
Section: Discussionmentioning
confidence: 99%